(untitled) (Eurasian Journal of History, Geography and Economics, 2021)
This article examines at the irrigation system and agricultural changes in Khorasan during the reign of Husayn Bayqara, as well as the role of Mirak Said Giyas, chief agronomic, horticultural, and landscape architect, in agriculture and horticulture development. A study of irrigation systems under Husayn Bayqara’s reign adds to the historical record.